DISABKIDS® in Brazil: advances and future perspectives for the production of scientific knowledge - Viviane Romeiro; Monika Bullinger; Maria Helena Palucci Marziale; Claudia Fegadolli; Roberta Alvarenga Reis; Renata Cristina de Campos Pereira Silveira; Moacyr Lobo da Costa-Júnior; Fátima Aparecida Emm Faleiros Sousa; Valéria Sousa de Andrade; Beatriz Juliana Conacci; Fernanda Karla Nascimento; Claudia Benedita dos Santos (Universidade de São Paulo, 2020)
Objective: to map the Brazilian scientific production related to the stages of the methodological process for the use of DISABKIDS® instruments and/or forms adapted to Brazil. Method: scoping review, with searches conducted on10 electronic databases, plus Google Scholar and contacts with researchers, without restriction of period or language. Results: the mapping identified 90 scientific studies involving 46 instruments. Of these, 11 (23.9%) included the elaboration and/or cultural adaptation of the DISABKIDS® instruments to measure the Quality of Life of children or adolescents with chronic conditions and 35 (76.1%) used the Generic Measures and/or Specific Modules for the semantic validation of other instruments. Conclusion: this scoping review allowed a comprehensive evaluation of the use of the DISABKIDS® instrument and forms, in relation to the validation of the instrument adapted to Brazil, presenting a positive advance in the scenario with the development of academic/scientific projects in the country, incorporating the method recommended by the literature for the elaboration, cultural adaptation and validation of instruments and for the systematized and standardized recording of the perception and understanding of the target population about the measure of interest, using DISABKIDS® forms adapted for this purpose.